Pengaruh Pemberian Informasi Obat terhadap Kepuasan Pasien serta Faktor Pengganggu yang Terlibat di Padangsambian, Bali - Sutrisnawati, Ni Komang Ayu Bintang; Agustini, Ni Putu Dewi; Mendra, Ni Nyoman Yudianti; Antari, Ni Putu Udayana (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Providing information when dispensing medicine is a pharmaceutical service that must follow applicable regulations. The best service makes patients satisfied and loyal to the pharmacy. Many things influence patient satisfaction due to varying patient perceptions regarding the quality of pharmacy services. This study aims to analyze the relationship between providing drug information and patient satisfaction, as well as confounding variables. Cross-sectional research was carried out by distributing Likert scale questionnaires and a checklist of types of drug information provided by pharmaceutical staff at the Indobat Padangsambian Pharmacy. The questionnaire was developed from literature studies and has been tested for validity and reliability. A total of 118 respondents who met the criteria were taken using convenience sampling techniques. Data were analyzed using descriptive statistics, chi-square test, and logistic regression. The chi-square test shows that the type of drug information conveyed by pharmaceutical staff is not related to patient satisfaction at the Indobat Padangsambian Pharmacy (p-value 0.580, CI 95%). All variables that are thought to be confounding variables do not have an independent effect on the dependent variable. However, it is known that occupation (health workers and non-health workers) and the patient's proximity to pharmaceutical workers interact and influence patient satisfaction. Pharmacy personnel should provide drug information according to regulations. To make patients satisfied and loyal to the pharmacy, pharmaceutical staff must pay attention to the patient's work background and personal relationship with the patient when providing drug information.